25th ANNIVERSARY OF CLONING BY SOMATIC-CELL NUCLEAR TRANSFER: Nuclear transfer and the development of genetically modified/gene edited livestock. Issue 1 (11th June 2021) - Alberio, Ramiro; Wolf, Eckhard
Abstract : The birth and adult development of 'Dolly' the sheep, the first mammal produced by the transfer of a terminally differentiated cell nucleus into an egg, provided unequivocal evidence of nuclear equivalence among somatic cells. This ground-breaking experiment challenged a long-standing dogma of irreversible cellular differentiation that prevailed for over a century and enabled the development of methodologies for reversal of differentiation of somatic cells, also known as nuclear reprogramming. Thanks to this new paradigm, novel alternatives for regenerative medicine in humans, improved animal breeding in domestic animals and approaches to species conservation through reproductive methodologies have emerged. Combined with the incorporation of new tools for genetic modification, these novel techniques promise to (i) transform and accelerate our understanding of genetic diseases and the development of targeted therapies through creation of tailored animal models, (ii) provide safe animal cells, tissues and organs for xenotransplantation, (iii) contribute to the preservation of endangered species, and (iv) improve global food security whilst reducing the environmental impact of animal production. This review discusses recent advances that build on the conceptual legacy of nuclear transfer and – when combined with gene editing – will have transformative potential for medicine, biodiversity and sustainable agriculture. We conclude that the potential of these technologies depends on further fundamental and translational research directed at improving the efficiency and safety of these methods.